PERAN KANTOR URUSAN AGAMA DALAM PENANGANAN ALIRAN SEMPALAN: STUDI KASUS KUA KECAMATAN TANJUNG BATU - Jaya, Agus (Jurnal Bimas Islam, 2015)
Abstract The emergence of White Chicken recitation sect in the district of Tanjung Batu Ogan Ilir of South Sumatra Province, Indonesia caused unrest in society. In a study obtained a description that the factors causing the spread of these sect are the lack of understanding of the true Islamic teaching, a false understanding of the religion concept and economic factors and the society phenomenon that easy to trust to instant promise. To tackle the spread of the sect, the Religious Affairs Office (KUA) of Tanjung Batu district makes three approaches include preventive approach, criminal law approach and the rehabilitative approach. With the commitment of "end to end" completed preventive approach, completed criminal law approach and completed rehabilitative approach, makes the handling of deviant sect specifically of White Chicken recitation sect in the working area of the Religious Affairs Office (KUA) of Tanjung Batu district was successfully managed.   Abstraksi Kemunculan aliran Pengajian Ayam Putih di kecamatan Tanjung Batu Kabupaten Ogan Ilir Provinsi Sumatera Selatan Indonesia telah menimbulkan keresahan di masyarakat. Dalam kajian diperoleh gambaran bahwa faktor penyebab menyebarnya aliran tersebut antara lain kurangnya pemahaman tentang agama Islam yang benar, pemahaman yang keliru terhadap konsep agama, faktor ekonomi dan fenomena masyarakat mudah percaya janji instan. Untuk menanggulangi penyebaran aliran tersebut, maka Kantor Urusan Agama (KUA) Kecamatan Tanjung Batu melakukan tiga pendekatan, yaitu pendekatan preventif, pendekatan hukum pidana dan pendekatan rehabilitatif. Dengan adanya komitmen ?end to end? yaitu tuntas pendekatan preventif, tuntas pendekatan hukum pidana dan tuntas pendekatan rehabilitatif, maka penangan aliran sesat secara khusus aliran Pengajian Ayam Putih di wilayah kerja Kantor Urusan Agama (KUA) Kecamatan Tanjung Batu berhasil dengan sukses.